Effect of Compaction Temperature Variations on the Characteristics of Marshall Asphalt Concrete-Wearing Course [AC-WC] using Modified Asphalt (Asphalt Pertamina PEN 60/70 with Addition of 1.5% Styrofoam) - Sakti Wibowo, Ramadhan (ASTONJADRO, 2023)
The road is one of the transportation infrastructures which is a basic need in community activities. Along with the development of road construction, road construction materials are needed that are more environmentally friendly and can improve the quality of the asphalt mixture. Styrofoam is one of the materials that can be added because styrofoam is a thermoplastic material. The compaction temperature is also a factor that it must consider during the implementation in the field because it will determine the level of asphalt stability. This research was conducted by an experimental method using modified asphalt with a mixture of 1.5% styrofoam. The optimum asphalt content used is 6%, with compaction temperatures of 80°C, 90°C, 100°C, 110°C, and 120°C based on the plot of the Bitumen Test Data Chart (BTDC). The data analysis is based on the results of the Marshall parameter values. The test uses asphalt inspection test equipment and Marshall test equipment. The results of this study are that the lower the compaction temperature, the smaller the Marshall parameter value, and the higher the compaction temperature, the higher the Marshall parameter value. Asphalt parameters decreased. Based on the Marshall test carried out, the compaction temperature that meets the requirements of the 2018 Highways specification from a temperature range of 80°C to 120°C with an interval of 10 C is at a temperature of 110ËšC and 120ËšC.